China's Economic Transformation Strategy: A Model for Papua New Guinea Development - Wakia, Betty (International Journal of Economics, Business Management and Accounting (IJEBMA), 2025)
Before 1978, China was indisputably among the most destitute countries globally and was on the brink of total macroeconomic failure. Therefore, in 1978, the nation implemented a market-oriented economic reform and has since emerged as the world's fastest-expanding economy. When adjusted for buying power parity, China's GDP has surpassed that of any other country in the world and it ranks second in nominal GDP, behind only the US. In spite of its vast natural resource endowment, achieving development in PNG has proven to be elusive. Although PNG specializes in crude oil production in the Pacific region and ranks 42nd globally, it is now one of the world's poorest nations. This report analysed China's economic reform effort and its potential applicability as a model for growth in PNG. Among other things, the nation's present economic woes have turned it into a crippled giant, and this research suggested that corruption and leadership failure are to blame. This study used the documentary approach, and the data produced were subjected to qualitative analysis. The analytical discussion revealed that robust economic plans or policies, along with exceptional or visionary leadership, laid the foundation for China's economic feats. Thus, the study proposes that the present underdeveloped state of PNG's economy may be improved by putting in place efficient government, excellent leadership, more funding for education and the development of human capital, and the organization of subsistence farming into cooperative societies. Therefore, the elimination of poverty, which is linked to inadequate governance, would be eradicated, and the typical mindset of the political elite in PNG of transforming the nation into a means of accumulating money would be abandoned